COVID-19 vaccination rates and factors affecting vaccination in children with rheumatic disease - Tuncay Aydın; Gülcan Özomay Baykal; Cüneyt Karagöl; Fatih Haşlak; Ebru Oğultekin Vazgeçer; Rüya Torun; Zehra Kızıldağ; Elif Kılıç Könte; Esma Aslan; Vildan Güngörer; et al. (Archives of Rheumatology, 2024)
Objectives: This study aimed to investigate coronavirus disease 2019 (COVID-19) vaccination rates and factors affecting vaccination in children with rheumatic diseases. Patients and methods: This multicenter cross-sectional survey-based study was conducted between July 2022 and September 2022. Four hundred seventy-four patients (256 females, 218 males; median age: 15 years; interquartile range, 13 to 16 years) were included in the patient group, and 211 healthy children (124 females, 87 males; median age: 15 years; interquartile range, 13 to 16 years) were included in the control group. A questionnaire was administered to the parents face-to-face during routine outpatient visits. Results: Of the patients, 220 were followed up with the diagnosis of autoinflammatory disease, 174 with juvenile idiopathic arthritis, 48 with connective tissue disease, 23 with vasculitis, eight with uveitis, and one with sarcoidosis. In the study group, 256 (54%) patients and 115 (54.5%) healthy children received at least one dose of COVID-19 vaccine. Parents’ concern regarding potential side effects of the vaccine was the most common reason for COVID-19 vaccination hesitancy in both groups. The median patient age, follow-up period, colchicine treatment rates, childhood vaccination and influenza vaccination rates, median parental age, parental vaccination rate, and parental education level were higher in vaccinated patients (p<0.001). Conclusion: Parents’ concerns about safety and side effects were found to be the most important factors affecting vaccination success. Identification of the underlying causes of parental vaccine hesitancy will facilitate the development of effective vaccination strategies for potential future outbreaks.